Relationship Between Heart Rate and Perceived Exertion in Neuromuscular Diseases: How do Laboratory-Based Exercise Testing Results Translate to Home-Based Aerobic Training Sessions? - Eric L. Voorn; Sander Oorschot; Tim Veneman; Bart Raijmakers; Frans Nollet (Medical Journals Sweden, 2023)
Objective: To examine the heart rate-perceived exertion relationship between maximal exercise testing and home-based aerobic training in neuromuscular diseases. Design: Multicentre randomized controlled trial, intervention group data. Participants: Individuals with Charcot-Marie-Tooth disease (n = 17), post-polio syndrome (n = 7) or other neuromuscular diseases (n = 6). Methods: Participants followed a 4-month, homebased aerobic training programme guided by heart rate. Heart rate and ratings of perceived exertion (6-20 Borg Scale) were assessed for each minute during a maximal exercise test, and at the end of each exercise interval and recovery period during training. Heart rate and corresponding ratings of perceived exertion values of individual participants during training were visualized using plots, together with the exercise testing linear regression line between heart rate and ratings of perceived exertion. Results: High correlation coefficients (i.e. > 0.70) were found between heart rate and ratings of perceived exertion, in all participants during testing (n = 30), and in 57% of the participants during training. Based on the plots the following distribution was found; participants reporting lower (n = 12), similar (n = 10), or higher (n = 8) ratings of perceived exertion values for corresponding heart rates during training compared with testing. Conclusion: Most participants had a different perception of effort for corresponding heart rates during training in comparison with exercise testing. Healthcare professionals should be aware that this may imply under- and over-training. LAY ABSTRACT Aerobic training, also called endurance training, is usually guided by target heart rate ranges based on exercise testing results. It is not known how the perception of effort for the same heart rate during a training programme relates to the perceived effort during exercise testing in people with neuromuscular diseases. This is important information for healthcare professionals. For instance, if patients report a higher perceived effort during training, this may explain their difficulties reaching target heart rate ranges. Maximal exercise testing and training data from 30 individuals with neuromuscular diseases were analysed. Most participants reported lower (10 participants) or higher (8 participants) perceived effort values for similar heart rates during training compared with exercise testing. Healthcare professionals in neuromuscular rehabilitation should be aware that this may indicate too low loads in some individuals and too high loads in others. This requires evaluation in further research.